Level control of process control / Anwar Zharif Azhar - Azhar, Anwar Zharif (2022)
The Final Year Project consists of a level control process in control system which basically pumps up the water in a sump tank to the process vessel. The experiment will be conducted in order to identify and analyse the inflow and outflow control of the water level. The main reasons that the students are having problems solving with this study of project is the reason why the project should be experimented. The experiment is to find the objectives as to how this project prevents and create safety by using different flow ranges of inflow and outflow with an open loop or closed loop.